A new wave spectrum resembling procedure based on ship motion analysis. (1st April 2020) - Piscopo, V.; Scamardella, A.; Gaglione, S.
Abstract: A new wave spectrum resembling procedure, based on two subsequent steps, is developed to detect the sea state parameters, namely the wave peak period, the significant wave height and the wave spectrum shape parameter, based on the analysis of heave and pitch motion time series, obtained by onboard measurements. The outlined procedure is applied to the S175 containership, assumed as reference vessel, and a set of basic conditions, with different vessel speeds, heading angles and sea state parameters, is preliminarily investigated. In this respect, heave and pitch motion time histories were obtained by time-domain simulations, based on theoretical wave spectra, in order to systematically investigate the reliability of the proposed procedure. Subsequently, a wide benchmark study is carried out, based on random generation of wave peak periods, significant wave heights and vessel speeds at four heading angles, equally spaced from head to following seas, in order to investigate the incidence of time duration on resembled sea state parameters. Finally, the statistics of errors on wave peak periods and significant wave heights are analysed to select the proper time duration of onboard measurements that allows balancing the reliability of resembled data with the need of an almost real-time sea state monitoring. Highlights: New wave spectrum resembling procedure based on heave and pitch motion analysis. Detection of the wave peak period and significant wave height. Benchmark study on the S175 containership. Incidence of recording time duration and statistics of errors. Solution of the combined heave/pitch motion equations in the frequency and time-domain.